2022
DOI: 10.1093/mnras/stac414
|View full text |Cite
|
Sign up to set email alerts
|

TESS asteroseismology of the Kepler red giants

Abstract: Red giant asteroseismology can provide valuable information for studying the Galaxy as demonstrated by space missions like CoRoT and Kepler. However, previous observations have been limited to small data sets and fields-of-view. The TESS mission provides far larger samples and, for the first time, the opportunity to perform asteroseimic inference from full-frame images full-sky, instead of narrow fields and pre-selected targets. Here, we seek to detect oscillations in TESS data of the red giants in the Kepler … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 61 publications
(74 reference statements)
3
26
0
Order By: Relevance
“…Clementini et al 2019;Mowlavi et al 2018;Ripepi et al 2022;Gaia Collaboration et al 2019), but its capacity has not yet been established for the low-amplitude main sequence IHM stars. While the µmag-precision space mis-sions so far resulted in asteroseismic modelling of thousands of red giants (Hon et al 2018;Yu et al 2018Yu et al , 2020Yu et al , 2021Stello et al 2022) and of hundreds of Sun-like dwarfs with masses M ≤ 1.3 M (García & Ballot 2019), the samples of asteroseismically modelled IHM dwarfs are much smaller and do not yet fully cover the parameter space in terms of rotation, binarity, and metallicity. It is in this area that Gaia's time series is helpful and will allow for the discovery of thousands of oscillating IHM candidates, with the aim being to achieve unbiased and complete samples.…”
Section: Introductionmentioning
confidence: 99%
“…Clementini et al 2019;Mowlavi et al 2018;Ripepi et al 2022;Gaia Collaboration et al 2019), but its capacity has not yet been established for the low-amplitude main sequence IHM stars. While the µmag-precision space mis-sions so far resulted in asteroseismic modelling of thousands of red giants (Hon et al 2018;Yu et al 2018Yu et al , 2020Yu et al , 2021Stello et al 2022) and of hundreds of Sun-like dwarfs with masses M ≤ 1.3 M (García & Ballot 2019), the samples of asteroseismically modelled IHM dwarfs are much smaller and do not yet fully cover the parameter space in terms of rotation, binarity, and metallicity. It is in this area that Gaia's time series is helpful and will allow for the discovery of thousands of oscillating IHM candidates, with the aim being to achieve unbiased and complete samples.…”
Section: Introductionmentioning
confidence: 99%
“…The high-precision photometric data provided by Kepler (e.g., Borucki et al 2010;Koch et al 2010) provides an unprecedented opportunity to explore stellar interiors by using the natural oscillation mode of stars, thus greatly expanding the research field of asteroseismology (e.g., Aerts et al 2010;Chaplin et al 2010;Xue et al 2018;Bowman et al 2021). The ultra-high-precision photometric observations at the μ mag level have significantly advanced our understanding of several types of pulsating variable stars (e.g., Balona et al 2012;Silva Aguirre et al 2015;Stello et al 2022;Szewczuk et al 2022). Bedding et al (2011) proposed that the observed period spacings of gravity modes could be applied to distinguish the hydrogen and helium burning stars in red giants.…”
Section: Introductionmentioning
confidence: 99%
“…The long time span of the Kepler mission has presented unprecedented frequency resolution, which allows us to detect new stellar features. The TESS mission covers the full sky and is capable of detecting stars closer and brighter than the typical Kepler targets (Stello et al 2021). The sky overlapping between the Kepler and TESS mission is well suited for carrying out astroseismology, as longer time-span data allows detection of more details, more frequencies, which potentially can be used to derive better constraints on the internal structure.…”
Section: Introductionmentioning
confidence: 99%